TECNOLOGIAS DA INFORMAÇÃO E COMUNICAÇÃO NA FORMAÇÃO DOCENTE INICIAL: um estudo no curso de Pedagogia da UFMA - Baima, Elke Trindade de Matos (2014)
The objective of this study is to investigate the integration of information and communication technologies in pedagogy course at the Federal University of Maranhão, from the study of the theoretical and methodological elements present in the course curriculum that guide initial teacher training. between the specific objectives include: understand the movement of ICT integration in education policies that contribute to current setting of initial teacher training; discuss the relationship of the education program of the course with ICT in initial teacher training; identify the perception of teachers and students about the development of the discipline Applied Informatics Education. Research has focused on initial teacher training related to the new demands required in this process to teaching due to the incorporation of information and communication technologies in the activity of a trader. Uses a qualitative approach and to give theoretical and methodological sutentabilidade, we make use of the contribution of scholars, including: Brzezinski(2008a, 2008b), Kuenzer (1999; 2000), Freitas (2002; 2003; 2007), Cabral neto e Castro (2005), Castells(1999), Frigotto (2001), Apple (1994), Goodson (2008), Sacristán (1998), Imbernon (2011), Coelho (1996), Ramalho, Nunes e Gauthier (2004), Barreto (2002; 2003; 2004; 2005;2006); Kenski (1998; 2008), Pontes e Varandas (2013). The literature and documentary allowed us to identify the configuration of the integration of ICT in initial teacher education, subsidized by the application of semi-structured interviews the teachers who teach the discipline and students of Pedagogy, also apply to these questionnaires. The study indicates that certain conditions in which it develops the discipline imposed on Computing Education blockers constitute factors for the achievement of the pedagogical function of these new Technologies. However, there is an undeniable requirement which is, in actuality, the incorporation of new technologies of information and communication the organization of curricula for teacher education, as well recognize the subjects of this research, students and teachers.